Appropriation of Eastern Notions from Cognitive Behavioral Therapy in Argentina - Korman, Guido Pablo; Saizar, Mercedes; Sarudiansky, Mercedes (Journal of Psychology and Psychotherapy Research, 2014)
In this study, the authors present the appropriation of Eastern notions in cognitive behavioral therapy in the Autonomous City of Buenos Aires, Argentina, inscribing this phenomenon on a wider field of interest for social science and psychotherapy. The supply of Eastern alternative therapies and the new developments of cognitive behavioral therapy in the area of study are introduced. Based on a survey conducted in CBT training institutions of the Autonomous City of Buenos Aires, three categories are proposed to understand the phenomena: 1) the desacralization of yoga; 2) the incorporation of Eastern traditions into cognitive behavioral psychotherapy, and 3) scopes and limits of therapeutic complementariness between cognitive behavioral therapy and Eastern practices. The authors conclude that this appropriation produces a desacralization of the original contents of the Eastern tradition, because in this fusion the focus is on the practice that produces well-being more than on the Eastern practices.